Posterior Corneal Changes after Photorefractive Keratectomy (PRK) in Pa-tient with Myopia Greater than 6 Diopters - Hassan Razmjoo; Akram Rismanchian; Amin Masjedi; Mohammad Sari Mohammadli (مجله دانشکده پزشکی اصفهان, 2011)
Background: This study aimed to evaluate the changes of posterior corneal curvature after photorefractive keratectomy (PRK) in patient with myopia greater than 6 diopters. Methods: The study was conducted on 107 eyes of 57 patients with the preoperative spherical equivalent refractive error of at least minus six diopters. Subjects underwent PRK for treatment of myopia or myopic astigmatism and were followed 4 months later to evaluate their refractive error. The posterior corneal curvature was evaluated by orbscan II topography preoperatively and 4 months after PRK. Finding: The diameter of posterior corneal best-fitted sphere (BFS) in 3, 5, 7 and 10 millimeter zones before surgery was 6.089 ± 0.2666, 6.137± 0.253, 6.299 ± 0.268, and 6.506± 0.312 millimeters respectively and after surgery these values had changed to 5.673± 0.362, 5.809± 0.341, 6.056± 0.309, and 6.347± 0.334 millimeters respectively. Conclusion: PRK for treatment of high myopia makes significant changes in the diameter of all measured zones of posterior cornea. The amount of alteration changed with regard to the selected zone, with the maximum effect in 3 and minimum effect in 10 millimeter zones.